2008
DOI: 10.1051/0004-6361:20079301
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron self-absorption in the GPS radio galaxy B0108+388

Abstract: Context. The compact radio source in the nucleus of the GPS radio galaxy B0108+388 consists of two jets that have spectra that turn over at frequecies lower than ∼5 GHz. There is evidence that the spectral turnover in B0108+388 results from free-free absorption by non-uniform thermal plasma in central tens of parsecs. Aims. To reveal the real cause of the low frequency cutoff in the jet spectra, it is necessary to consider different mechanisms and, in particular, syncrotron self-absorption. Methods. We suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We note that a magnetic field as large as B(−2) = 10 (e.g. Artyukh et al 2008) would reduce the required U o to a more reasonable 3 − 4%, but this would still have to be removed by an inhomogeneous, depolarizing screen to satisfy our limit. Finally we calculate Stokes Q in the same approximation and limit.…”
Section: E1 the Case Of Small Faraday Depthmentioning
confidence: 92%
See 2 more Smart Citations
“…We note that a magnetic field as large as B(−2) = 10 (e.g. Artyukh et al 2008) would reduce the required U o to a more reasonable 3 − 4%, but this would still have to be removed by an inhomogeneous, depolarizing screen to satisfy our limit. Finally we calculate Stokes Q in the same approximation and limit.…”
Section: E1 the Case Of Small Faraday Depthmentioning
confidence: 92%
“…For ν 5 = 1 (a spectral turnover of 5 GHz, Fig. 6), for fields even as large as 0.04 G (a comfortable upper limit, see Artyukh et al 2008) the lifetime of particles radiating at the spectral turnover is about 58 years and γ e = 173. Higher energy particles by about a factor of one hundred would be evolving substantially.…”
Section: Spectral Evolution Of a Simple Ensemble Of Relativistic Ementioning
confidence: 99%
See 1 more Smart Citation
“…Ubachukwu, Okoye & Onuora 1991, and references therein). Assuming lobe confinement by ram‐pressure balance with the external medium, then we have (Ubachukwu et al 1991; Fanti et al 1995; Readhead et al 1996; Carvalho 1998; Artyukh, Chernikov & Tyul'bashev 2008; Labiano 2008; Orienti & Dallacasa 2008) where P i is lobe internal pressure, n e is external medium density and m H is proton mass. Using , it can be shown that the kinetic power, P cj , delivered by the core to the jet can be expressed according to the following relation (see also Carvalho 1998): where Ω is jet opening solid angle and c is light speed.…”
Section: Dependence Of Linear Size On the Density Of The Ambient Mementioning
confidence: 99%
“…Ubachukwu, Okoye & Onuora 1991, and references therein). Assuming lobe confinement by ram-pressure balance with the external medium, then we have (Ubachukwu et al 1991;Fanti et al 1995;Readhead et al 1996;Carvalho 1998;Artyukh, Chernikov & Tyul'bashev 2008;Labiano 2008;Orienti & Dallacasa 2008)…”
Section: E P E N D E N C E O F L I N E a R S I Z E O N T H E D E N mentioning
confidence: 99%